Digitising command and control : a human factors and ergonomics analysis of Mission Planning and Battlespace management /: a human factors and ergonomics analysis of Mission Planning and Battlespace management. (2017) - Stanton, Neville A (Neville Anthony), 1960-; Jenkins, Daniel P; Salmon, Paul M; Walker, Guy; Revell, Kirsten M. A; Rafferty, Laura A
No abstract available